Implant Reconstruction in Nipple Sparing Mastectomy - Chu, Carrie K.; Davis, Matthew J.; Abu-Ghname, Amjed; Winocour, Sebastian J.; Losken, Albert; Carlson, Grant W. (Seminars in Plastic Surgery, 2019)
Nipple sparing mastectomy has been popularized in the modern era of breast cancer treatment due to its touted advantages with regard to resultant body image and reconstructive outcome. Implant-based techniques remain the most prevalent means of breast reconstruction. Special considerations regarding patient selection and technique are reviewed for implant reconstruction in the setting of mastectomy with nipple preservation. Applications for prepectoral and direct-to-implant reconstruction are discussed and published outcomes are summarized.
Keywords: nipple sparing mastectomy; breast reconstruction; implants; breast cancer